2008
DOI: 10.1016/j.chemosphere.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and availability of arsenic in soils from the industrialized urban area of Beijing, China

Abstract: a b s t r a c tConcentrations of arsenic (As) were determined in soils of 5 industrial sites in an urban area of Beijing, China. Fifty seven typical surface soils were sampled to determine total concentrations of metals, pH and dissolved organic carbon (DOC). One hundred and eight deep soils were submitted to a four-step, sequential extraction to assess the relative mobility and bioavailability of As in the soil profiles. Total concentrations of As in surface soils ranged from 5.7 to 2.3 Â 10 1 mg kg À1 , dw w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…In order to estimate the extent of As-dust pollution of Pakistani environment, the mean values of all the studied land use settings were considered and compared with the global data reported from previous studies (Table 3). Arsenic levels in the present study were higher than those reported from UK (Okorie et al, 2012) and Angola (Ferreira-Baptistaa and de Miguel, 2005) but comparable and/or lower than those reported from India (Sanz et al, 2007), Greece (Achilleas and Nikolaos, 2009), Spain and Switzerland (Amato et al, 2011), USA (Landrot et al, 2012), and China (Luo et al, 2008;Hu et al, 2011).…”
Section: Arsenic Levels In Dust Samplescontrasting
confidence: 64%
“…In order to estimate the extent of As-dust pollution of Pakistani environment, the mean values of all the studied land use settings were considered and compared with the global data reported from previous studies (Table 3). Arsenic levels in the present study were higher than those reported from UK (Okorie et al, 2012) and Angola (Ferreira-Baptistaa and de Miguel, 2005) but comparable and/or lower than those reported from India (Sanz et al, 2007), Greece (Achilleas and Nikolaos, 2009), Spain and Switzerland (Amato et al, 2011), USA (Landrot et al, 2012), and China (Luo et al, 2008;Hu et al, 2011).…”
Section: Arsenic Levels In Dust Samplescontrasting
confidence: 64%
“…The Mo and As atom substitutions in the structure of feldspar and phyllosilicate group minerals are not reported (Deer et al, 1992) so, in the raw materials, the Mo and As undigested are in the structure of minerals in quantities not detectable by XRD and/or forming part of the amorphous/vitrified material and they could be the sources of the increase in the concentrations of molybdenum and arsenic bound to the nonresidual fraction in both types of LWAs. The transformation of residual As into more mobile chemical forms is a common consequence of exposure to the high temperatures of As-bearing materials, such as fossil fuel (Luo et al, 2008). Consequently, special care should be taken when the potential raw materials of LWAs have high concentrations of Mo and As since, after thermal treatment, they will be more available in the LWAs than in the raw materials.…”
Section: Erxy 3f(3) Mixture Vs 3f(3)-1150-15mentioning
confidence: 98%
“…The main factors affecting arsenic concentrations in soils are rock composition and human activities such as mining (Bhattacharya et al 2007, and references therein), smelting and power plants (Luo et al 2008), combustion of fossil fuels , and agriculture, pesticides and herbicides (Bhattacharya et al 2007;Nicholson et al 2003). However, the parent material is frequently considered to be the most important factor affecting arsenic content (Ungaro et al 2008).…”
Section: Ef Sc For Total Metal Concentrationsmentioning
confidence: 98%